Importance of Hepatic Transporters in Clinical Disposition of Drugs and Their Metabolites. (July 2016) - Patel, Mitesh; Taskar, Kunal S.; Zamek‐Gliszczynski, Maciej J.
Abstract: This review provides a practical clinical perspective on the relevance of hepatic transporters in pharmacokinetics and drug‐drug interactions (DDIs). Special emphasis is placed on transporters with clear relevance to clinical DDIs, efficacy, and safety. Basolateral OATP1B1 and 1B3 emerged as important hepatic drug uptake pathways, sites for systemic DDIs, and sources of pharmacogenetic variability. As the first step in hepatic drug removal from the circulation, OATPs are an important determinant of systemic pharmacokinetics, specifically influencing systemic absorption, clearance, and hepatic distribution for subsequent metabolism and/or excretion. Biliary excretion of parent drugs is a less prevalent clearance pathway than metabolism or urinary excretion, but BCRP and MRP2 are critically important to biliary/fecal elimination of drug metabolites. Inhibition of biliary excretion is typically not apparent at the level of systemic pharmacokinetics but can markedly increase liver exposure. Basolateral efflux transporters MRP3 and MRP4 mediate excretion of parent drugs and, more commonly, polar metabolites from hepatocytes into blood. Basolateral excretion is an area in need of further clinical investigation, which will necessitate studies more complex than just systemic pharmacokinetics. Clinical relevance of hepatic uptake is relatively well appreciated, and clinical consequences of hepatic excretion (biliary and basolateral) modulation remain an active research area.